Institution and Communities Participation in the Conservation Of Mangrove/Case Study in Tiwoho Village, North Province - Lis Nurrani; M Bismark; Supratman Tabba (Jurnal Wasian, 2015)
Institutional and community participation is an important aspect being the main pillar in the implementation of the rehabilitation of mangroves. There is rarely any failure in the mangrove rehabilitation because it is not supported by the institutional role to its full potential. This research aimed to inventory the role of institutions and community participation in mangrove conservation in the coastal zone, Tiwoho Village, North Sulawesi Province. Selection of study areas and respondents done by purposive sampling. Data colected by field observation and structured interview with key respondents by using the snawball method. Research showed that some institutions has a major contribution in initiating mangrove conservation in Tiwoho are public figures, village government, NGOs, religious institutions, institutions of formal education, and foreign researcher. The form of community participation in conserving mangrove among others are not cut down of mangrove wood for any reason planting seeds every oportunity and keep mangrove from other community disturbances. Several method of management are expected to be inspiration for stakeholders to be able developed a mangrove forest management system in different place which have similar characteristics.